2022
DOI: 10.1093/bioinformatics/btac447
|View full text |Cite
|
Sign up to set email alerts
|

LRLoop: a method to predict feedback loops in cell–cell communication

Abstract: Motivation Intercellular communication (i.e. cell-cell communication) plays an essential role in multicellular organisms coordinating various biological processes. Previous studies discovered that feedback loops between two cell types are a widespread and vital signaling motif regulating development, regeneration, and cancer progression. While many computational methods have been developed to predict cell-cell communication based on gene expression datasets, these methods often predict one-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Further, in-depth analysis revealed several differentially expressed genes in the RPE and microglial cells ( Figure 3 b,c). To pinpoint the signaling molecules associated with RPE–microglia interaction in the disease state of this mouse model, we performed a novel ligand-receptor (LR) loop bioinformatic analysis [ 25 ] that showed several interactive partners linking RPE (Ligand; L) and microglia (Receptor; R) in 15-month-old Cryba1 fl/fl and Cryba1 cKO ( Figure 3 d). The LR loop interaction between RPE and microglia revealed a notable increase in the interactions between cognate ligands from RPE cells (such as CXCL12 and Col4a3) and their respective cell surface receptors such as Itgb1 and CD47 on microglia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, in-depth analysis revealed several differentially expressed genes in the RPE and microglial cells ( Figure 3 b,c). To pinpoint the signaling molecules associated with RPE–microglia interaction in the disease state of this mouse model, we performed a novel ligand-receptor (LR) loop bioinformatic analysis [ 25 ] that showed several interactive partners linking RPE (Ligand; L) and microglia (Receptor; R) in 15-month-old Cryba1 fl/fl and Cryba1 cKO ( Figure 3 d). The LR loop interaction between RPE and microglia revealed a notable increase in the interactions between cognate ligands from RPE cells (such as CXCL12 and Col4a3) and their respective cell surface receptors such as Itgb1 and CD47 on microglia.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the extent that microglia activate neutrophils or how these immune cells interact with each other during AMD progression in the SRS remains unclear. To understand the dynamic interactions between these immune cells, we used LR loop bioinformatic analysis [ 25 ], which showed several interactive partners linking microglia and neutrophils and several differentially expressed microglial ( Figure 3 c) and neutrophil ( Figure 5 a) genes. Interestingly, we found that both CD14 (microglia)/integrin β1 (Itgβ1) (neutrophil) and CD14/integrin α4 (Itgα4) interactions were upregulated in Cryba1 cKO retina ( Figure 5 a,b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations